Fenarimol, a Pyrimidine-Type Fungicide, Inhibits Brassinosteroid Biosynthesis - Oh, Keimei (Int J Mol Sci, 2015)
The plant steroid hormone brassinosteroids (BRs) are important signal mediators that regulate broad aspects of plant growth and development. With the discovery of brassinoazole (Brz), the first specific inhibitor of BR biosynthesis, several triazole-type BR biosynthesis inhibitors have been developed. In this article, we report that fenarimol (FM), a pyrimidine-type fungicide, exhibits potent inhibitory activity against BR biosynthesis. FM induces dwarfism and the open cotyledon phenotype of Arabidopsis seedlings in the dark. The IC(50) value for FM to inhibit stem elongation of Arabidopsis seedlings grown in the dark was approximately 1.8 ± 0.2 μM. FM-induced dwarfism of Arabidopsis seedlings could be restored by brassinolide (BL) but not by gibberellin (GA). Assessment of the target site of FM in BR biosynthesis by feeding BR biosynthesis intermediates indicated that FM interferes with the side chain hydroxylation of BR biosynthesis from campestanol to teasterone. Determination of the binding affinity of FM to purified recombinant CYP90D1 indicated that FM induced a typical type II binding spectrum with a K(d) value of approximately 0.79 μM. Quantitative real-time PCR analysis of the expression level of the BR responsive gene in Arabidopsis seedlings indicated that FM induces the BR deficiency in Arabidopsis.